2018
DOI: 10.1108/jsbed-03-2017-0130
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agricultural entrepreneurship in Burundi: drivers and outcomes

Abstract: Purpose The purpose of this paper is to contribute to the emerging literature on sustainable entrepreneurship by studying knowledge, motivation and early stage outcomes of sustainable agricultural entrepreneurship in the context of farmer groups in Burundi. Design/methodology/approach Quantitative and qualitative data were combined in a multiple-source case study. Data were analyzed using content analysis and basic statistics. Findings Results revealed that farmer groups’ prior knowledge (PK) on environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 56 publications
2
51
0
Order By: Relevance
“…Based on a sample of 160 small fresh fruit farms located in inland Portugal, we deployed a partial least squares structural equation modeling (PLS-SEM) to analyze how dynamic capabilities (DCs), EO, and environmental sustainability commitment (ESC) are associated with improving the performance of farm businesses. Despite many entrepreneurs do not realize of their impacts on the environment and have few resources to respond to environmental challenges (Mupfasoni et al, 2018), our study found that EO and ESC have positive effects on EP and FP. Hence, small farms can establish competitive advantages through the improvement of environmental sustainability as proposed by the natural resource-based view (NRBV) (Hart & Dowell, 2011).…”
Section: Introductionmentioning
confidence: 55%
“…Based on a sample of 160 small fresh fruit farms located in inland Portugal, we deployed a partial least squares structural equation modeling (PLS-SEM) to analyze how dynamic capabilities (DCs), EO, and environmental sustainability commitment (ESC) are associated with improving the performance of farm businesses. Despite many entrepreneurs do not realize of their impacts on the environment and have few resources to respond to environmental challenges (Mupfasoni et al, 2018), our study found that EO and ESC have positive effects on EP and FP. Hence, small farms can establish competitive advantages through the improvement of environmental sustainability as proposed by the natural resource-based view (NRBV) (Hart & Dowell, 2011).…”
Section: Introductionmentioning
confidence: 55%
“…Consequently, the incorporation of technical learning areas creates sustainability value for entrepreneurs [40]. In that spirit, sustainable entrepreneurs serve as economic agents to initiate, adapt, and integrate those processes and activities which lead to the development of sustainability-driven and profitable economic opportunities [1].…”
Section: Sustainability Concerns and Sustainable Entrepreneurship In Agriculturementioning
confidence: 99%
“…An agriculture perspective of the planet emphasizes how management measures and environmental conditions affect yields and how these conditions can be improved based on the effects of plant growth and different conditions such as soil fertility, pests, and climate. It then focuses on maintaining or increasing current levels of biophysical productivity that can be achieved from agriculture sustainability [1,60]. The agriculture perspective of profit focuses on mass production as the main driving force behind the so-called green revolution, also known as industrialization or traditional agricultural model of a farm-level enterprise and an essential economic sector at the local, regional, national, and international levels.…”
Section: Triple Bottom Line and Sustainable Agriculture Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most potent tools for achieving this end is sustainable entrepreneurship (Fischer, Mauer, & Brettel, 2018). Sustainable entrepreneurship has been defined as the act of recognition, development and exploitation of opportunities to create goods and services with economic, social and environmental benefits (Mupfasoni, Kessler, & Lans, 2018). Sustainable entrepreneurs are entrepreneurs who take into account different aspects of social, economic and environmental sustainability in their entrepreneurial endeavors (Tilley & Parrish, 2006).…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%